Gastrointestinal Physiology Development, Principles and Mechanisms of Regulation - Welcome, Menizibeya Osain (Springer International Publishing, 2018)
This book offers one of the most comprehensive reviews in the field of gastrointestinal (GI) physiology, guiding readers on a journey through the complete digestive tract, while also highlighting related organs and glandular systems. It is not solely limited to organ system physiology, and related disciplines like anatomy and histology, but also examines the molecular and cellular processes that keep the digestive system running. As such, the book provides extensive information on the molecular, cellular, tissue, organ, and system levels of functions in the GI system. Chapters on the roles of the gut as an endocrine, exocrine and neural organ, as well as its microbiome functions, broaden readers' understanding of the multi-organ networks in the human body. To help illustrate the interconnections between the physiological concepts, principles and clinical presentations, it outlines clinical examples such as pathologies that link basic science with clinical practice in special "clinical correlates" sections. Covering both traditional and contemporary topics, it is a valuable resource for biomedical students, as well as healthcare and scientific professionals.